Pre-Service Teachers’ Perceptions of Canva as a Collaborative Learning Media for Primary Students in the Classroom - Habibah, Jihan Fara (Proceeding International Conference on Religion, Science and Education, 2025)
This study explored the views of pre-service teachers concerning the use of Canva as a collaborative learning media in elementary school classrooms. The current study investiagates the use of Canva on teachers’ and students’ relationships and looks into the benefits and challenges posed by Canva in educational settings. It also tends to analyze respondents’ experiences and views for a deeper understanding of how Canva enhances student collaboration in the learning process. This study employs qualitative methods whereby data are obtained using an online questionnaire using G-Form with open-ended questions to allow freedom of expression by the participants. The respondents were students from the third, fifth, and seventh semesters studying at one university in Surabaya, more precisely, in the English Education study program. It was found that with Canva, creativity is promoted with collaboration, which is all in line with educational theories such as those of Vygotsky, emphasizing the role of social interaction in learning. A few disadvantages were identified: students were not used to using it, and poor internet access sometimes created other problems. Such challenges are ably assisted by the teachers in the mentorship and guidance needed towards effective adaptation to the use of Canva. In this respect, the study consequently underlines an Instrumental implementation of such tools in education, so that all students can take advantage of their collaborative learning opportunities.